Effects of ultraviolet radiation on the microbiological, physicochemical, and sensory properties of rangpur lime juice - Acevedo, Belén Andrea (2018)
Fil: Acevedo, Belén Andrea. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.